Trajectory of Cardiovascular Risk Factors After Hypertensive Disorders of Pregnancy: An Argument for Follow-Up. Issue 1 (January 2019) - Groenhof, T. Katrien J.; Zoet, Gerbrand A.; Franx, Arie; Gansevoort, Ron T.; Bots, Michiel L.; Groen, Henk; Lely, A. Titia
Abstract : Women with a history of a hypertensive disorder of pregnancy (HDP) are at increased risk of premature cardiovascular disease. Cardiovascular risk management guidelines emphasize the need for prevention of cardiovascular disease in these women but fail to provide uniform recommendations on when and how to start cardiovascular risk assessment. The aim of this study was to identify a window of opportunity in which to start cardiovascular risk factor assessment by investigating changes in blood pressure, lipids, and fasting glucose levels over time in women with a history of an HDP. We identified women with a history of a normotensive pregnancy (n=1811) or an HDP (n=1005) within a high-risk population-based cohort study. We assessed changes in blood pressure, lipids, glucose, 10-year cardiovascular risk and the occurrence of hypertension, dyslipidemia, and diabetes mellitus longitudinally using 5 measurements at 3-year intervals. Generalized estimating equations were used for statistical analysis, with age as the time variable, adjusting for multiple comparisons using the least significant differences method. In women with an HDP, the overall prevalence of hypertension ( P <0.0001), dyslipidemia ( P =0.003), and diabetes mellitus ( P <0.0001) was significantly higher. They also developed hypertension and diabetes mellitus earlier. At age 35, few women with HDP need to be screened to detect clinically relevant hypertension: 9 need to be screened to detect 1 woman with a treatment indication as opposed to 38 women with history of a normotensive pregnancy. Our data supports cardiovascular follow-up of women with a history of an HDP starting within the fourth decade of life.